2020
DOI: 10.1101/2020.05.05.078097
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PARP12-catalyzed mono-ADP-ribosylation of Golgin-97 controls the transport of E-cadherin

Abstract: ADP-ribosylation is a post-translational modification involved in physiological and pathological events catalyzed by Poly-ADP-Ribosyl-Polymerase (PARP) enzymes. Substrates of this reaction have been identified by mass-spectrometry, but the definition of PARPs-regulated cellular functions remains scarce. Here, we have analyzed the control of intracellular membrane traffic by the mono-ADP-ribosyl-transferase PARP12, motivated by its localization at the trans-Golgi network. By using bioinformatics, mutagenesis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 84 publications
(93 reference statements)
0
4
0
Order By: Relevance
“… 19 Recent studies have indicated that MARylation of Golgin-97 is necessary to ensure the correct transport of E-cadherin from the reverse Golgi apparatus to the plasma membrane. 20 Inhibition of MARylation will prevent Golgin-97-controlled E-cadherin from reaching the plasma membrane and promote epithelial-mesenchymal transformation (EMT). Therefore, MARylation of different proteins in the cytoplasm causes the aggregation of intracellular β-catenin, a reduction in the binding of β-catenin to E-cadherin at the cell membrane, and the decreased distribution of E-cadherin to the plasma membrane, all of which lead to decreased adhesion between cells and an increased likelihood that tumor cells will infiltrate the surrounding microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Recent studies have indicated that MARylation of Golgin-97 is necessary to ensure the correct transport of E-cadherin from the reverse Golgi apparatus to the plasma membrane. 20 Inhibition of MARylation will prevent Golgin-97-controlled E-cadherin from reaching the plasma membrane and promote epithelial-mesenchymal transformation (EMT). Therefore, MARylation of different proteins in the cytoplasm causes the aggregation of intracellular β-catenin, a reduction in the binding of β-catenin to E-cadherin at the cell membrane, and the decreased distribution of E-cadherin to the plasma membrane, all of which lead to decreased adhesion between cells and an increased likelihood that tumor cells will infiltrate the surrounding microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…During their intracellular replication cycle, many viruses hijack cellular membrane trafficking mechanisms, such as the endocytic and the secretory pathways, for the transport of viral genomes or proteins throughout the cell [ 53 ]. Recently, PARP12 was shown to affect the intracellular trafficking of viral proteins, by promoting transport from the Golgi to the plasma membrane via ADP-ribosylation of Golgin-97 [ 49 , 54 , 55 ].…”
Section: Adp-ribosylation and Ifn-induced Effector Functionsmentioning
confidence: 99%
“…PARP12 is also a mono-ART of the PARP family, which controls the regulation of cell survival and regrowth ( Catara et al, 2017 ). The function of PARP12 is the mono-ADP-ribosyltransferase that mediates mono-ADP-ribosylation of target proteins, although the molecular mechanism responsible for cell survival is still unclear ( Catara et al, 2017 ; Grimaldi et al, 2020 ). Recently, PARP12 involvement in intracellular membrane transport at this point deserves much attention and alternative effective strategies ( Gozgit et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%